Smutgrass Control in Perennial Grass Pastures - Brent Sellers; Jason A. Ferrell; Neha Rana (EDIS)
Smutgrass is a serious weed of improved perennial grass pastures, roadsides, natural areas, and waste areas in Florida. A 2003 survey found that smutgrass was second only to tropical soda apple as the most problematic weed species in Florida pastures, but now that practices to control tropical soda apple have been widely adopted in Florida, smutgrass is likely the most problematic weed species in Florida pastures today. This revised 4-page fact sheet was written by Brent Sellers, J. A. Ferrell, and N. Rana, and published by the UF Department of Agronomy, January 2015. (Photo Credit: B. Sellers, UF/IFAS)